Registration of Illegitimate Children: Between Basic Rights and Islamic Legal Challenges in Malaysia: Registration of Illegal Children: Between Human Rights and Challenges of Islamic Law in Malaysia (Kanun: Jurnal Undang-undang Malaysia, 2023)
A legitimate identity from a legal point of view is essential because it is closely related to the protection of basic human rights to development, such as the right to life, health and education. However, illegitimate children in Malaysia, especially Muslims, often face discrimination due to their unregistered birth. This paper will examine the history of human rights development and provisions related to the protection of children’s rights, in particular the right to birth registration in the Convention on the Rights of the Child 1989 (CRC) and the Child Act 2001 [Act 611]. In addition, the position of illegitimate children in the Islamic Law is also described. This writing is a purely legal study with qualitative methods and content analysis. This paper concludes that among the challenges in Islamic Law that prevent the registration of childbirths in the country are marriage document requirements, stigma and social exclusion as well as lack of public awareness. Therefore, several ideas for improvement are proposed, namely amending the law, creating a special birth register for illegitimate children, simplifying the birth registration procedure as well as enhancing knowledge on the importance of birth registration in society.Keywords: Illegitimate children, basic rights, children, birth registration, registration procedure, Islamic lawFull text: PDF